Co-composting of biodegradable municipal waste (BMW) and fruit and vegetable waste (FVW) for environmental management - Mala, Musa Aishatu; Ishak, Che Fauziah; Karam Singh, Daljit Singh; Md Jaafar @ Ahmad Jaafar, Noraini (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Co-composting of municipal solid waste (MSW) and fruit and vegetable waste (FVW) was undertaken with a view to address the ever increasing problem of organic/ agricultural waste disposal to produce an improved compost that can be used on agricultural land. Open composting using 20 liter bins was employed in the composting of BMW and FVW in 3:1, 1:2 and 1:4 FVW: BMW with and without homemade effective microorganisms. The BMW consisted of rice, garden wastes (as recovered) and paper while the FVW consisted of fruit and vegetable wastes generated from the Pasar Borong market (fruit and vegetable market) in Serdang Selangor, Malaysia. Characterization of primary substrates used in the co-composting was done and the materials for composting were all chopped to sizes 3-5 cm, homemade effective microorganisms was applied to some of the treatment to adjust the moisture content while tap water was added to the rest of the treatment. Temperature and C: N and some other parameters of the composts were monitored for a period of 30 days. The compost was turned daily for the first two weeks and subsequently after three days. The temperature of the compost was highly significant at p<0.05 for treatments used, days of composting and also treatment by day. The C: N ratio at the end of the composting period is significantly different at p<0.05 for the different treatments used. The ratio with highest fruit and vegetable waste (3:1) had gone down to <15 while for the other treatments C: N was 21.15 at the end of the composting period from an initial mean C: N ratio of 41.2. The germination test carried out using corn showed non-significant results at p<0.05. It can be concluded that co-composting of BMW and FVW can be used as a means of addressing environmental pollution due to indiscriminate disposal of agricultural wastes and waste from homes with the provision of improved quality compost that can be used as an organic fertilizer on farms and gardens safely.